ENHANCING INFANT AND TODDLER EDUCATION: RESEARCH INTO EFFECTIVE TASKA METHODS ALIGNED WITH PARENT EXPECTATIONS - TENGKU ALIAA SYAIRAH BINTI TENGKU SALLEHUDDIN TENGKU; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Early childhood education in Malaysia is divided between TASKA (for children aged 0-4) and preschools (for children aged 4-6). TASKA centres play an essential role in providing nurturing care and early education for infants and toddlers. However, despite the growing awareness of the importance of early learning, TASKA centres in Malaysia still face challenges such as limited teacher training, unequal quality among urban and rural areas, and increasing parental expectations. This study explores the ways TASKA can strengthen infant and toddler education to align with parental aspirations and current educational trends. The findings show that TASKA has improved in areas of safety and health but must also prioritise holistic learning through play-based and interactive approaches. Strengthening teacher training, parent partnerships, and curriculum design will ensure that TASKA continues to meet the needs of Malaysian families and contributes to lifelong learning success.